2013
DOI: 10.1007/978-3-642-40925-7_24
|View full text |Cite
|
Sign up to set email alerts
|

The Removal of False Detections from Foreground Regions Extracted Using Adaptive Background Modelling for a Visual Surveillance System

Abstract: Abstract. For recent surveillance systems, the false detection removal process is an important step which succeeds the extraction of foreground regions and precedes the classification of object silhouettes. This paper describes the false object removal process when applied to the 'SmartMonitor' system -i.e. an innovative monitoring system based on video content analysis that is currently being developed to ensure the safety of people and assets within small areas. This paper firstly briefly describes the basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…4 Sample frames presenting the simulation of a crime scene (scenario C) [7] Fig . 5 General scheme of applied background subtraction process [13] H component of HSV colour scheme, which corresponds more closely to human perception. It was experimentally found that shadow darkens the region while the hue does not vary too much [16].…”
Section: Background Modelling and Foreground Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Sample frames presenting the simulation of a crime scene (scenario C) [7] Fig . 5 General scheme of applied background subtraction process [13] H component of HSV colour scheme, which corresponds more closely to human perception. It was experimentally found that shadow darkens the region while the hue does not vary too much [16].…”
Section: Background Modelling and Foreground Extractionmentioning
confidence: 99%
“…Since there are various types of false detections, the usage of only one foreground image decreases the possibility of distinguishing false objects from actual OOIs. Therefore, as already mentioned, the combination of two background models, namely intensity and chrominance (hue) models, was selected for the false detection removal process and investigated in [13].…”
Section: Background Modelling and Foreground Extractionmentioning
confidence: 99%
“…It can be utilized both inside and outside the building to increase security in houses, private apartments, nursing homes, small businesses or shops, as well as in backyards, gardens, parking spaces, building surroundings, especially near entrances or windows. “SmartMonitor” has already been described in literature [14]. …”
Section: Introductionmentioning
confidence: 99%